2019
DOI: 10.1002/jeab.567
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of treatment duration on the resurgence of destructive behavior

Abstract: Quantitative models of resurgence (e.g., Behavioral Momentum Theory, Resurgence as Choice) suggest that resurgence is partly a function of the duration of extinction exposure, with longer histories of extinction producing less resurgence. This prediction is supported by some laboratory research and has been partially supported by clinical translations that did not isolate the effects of extinction exposure prior to testing for resurgence. The degree to which different histories of extinction impact the likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Beyond providing support that varying phase duration had a predictable effect, this also suggests that there could be additive effects of phase durations. Although research in applied settings has not clearly demonstrated an effect of phase duration by manipulating the duration of a single phase in isolation (e.g., Greer et al, 2020;Lambert et al, 2020), our method of combining manipulations in both phases may prove helpful for research in more applied settings and may have important clinical implications. For example, this research may support the need for combining phase duration manipulations (i.e., earlier intervention for problem behavior, longer clinical admissions) to mitigate the possibility of treatment relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond providing support that varying phase duration had a predictable effect, this also suggests that there could be additive effects of phase durations. Although research in applied settings has not clearly demonstrated an effect of phase duration by manipulating the duration of a single phase in isolation (e.g., Greer et al, 2020;Lambert et al, 2020), our method of combining manipulations in both phases may prove helpful for research in more applied settings and may have important clinical implications. For example, this research may support the need for combining phase duration manipulations (i.e., earlier intervention for problem behavior, longer clinical admissions) to mitigate the possibility of treatment relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In another applied study with humans who engaged in destructive behavior, Fisher et al (2018) evaluated the effects of Phase 2 duration on resurgence; however, Phase 2 duration was manipulated in combination with two other resurgence-mitigation strategies (i.e., lower rates of reinforcement during baseline and treatment), making it difficult to draw conclusions regarding the effect of Phase 2 duration in isolation. Most recently, Greer et al (2020) evaluated the effect of Phase 2 duration in isolation with six participants who engaged in destructive behavior using a multielement design but failed to demonstrate a reliable effect within or across participants. Greer et al suggested that the lack of an effect may have been related to poor discrimination across the conditions in the multielement design, which is similar to one of the limitations of Lambert et al (2020).…”
mentioning
confidence: 99%
“…If problem behavior during each session before the change was 0, no proportion was calculated due to a zero denominator and these data were removed from this calculation. We also included a simple difference measure in order to account for cases in which problem behavior was at zero prior to the thinning step (e.g., Greer et al, 2020). For this difference measure, we calculated the average rate of problem behavior following each thinning step and subtracted the average rate of problem behavior before the thinning step; these differences were calculated across all observations regardless of whether resurgence was observed.…”
Section: Data Coding and Calculationsmentioning
confidence: 99%
“…Increased interest in the resurgence of destructive behavior has brought about a flurry of recent investigations on the prevalence, magnitude, and persistence of resurgence as it occurs in practice, as well as methods for mitigating such deleterious effects (Briggs et al, 2018;Brown et al, 2020;Fisher et al, 2018Fisher et al, , 2019Fisher et al, , 2020Fuhrman et al, 2016;Greer et al, 2020;Mitteer et al, in press;Muething et al, 2021). Studies on the prevalence of resurgence of destructive behavior during reinforcement schedule thinning have shown the phenomenon to be quite common.…”
mentioning
confidence: 99%